1997
DOI: 10.1183/09031936.97.10102312
|View full text |Cite
|
Sign up to set email alerts
|

Mucociliary clearance in cystic fibrosis knockout mice infected with Pseudomonas aeruginosa

Abstract: In this study, we examined whether mucociliary clearance differed between cystic fibrosis (CF) knockout mice and wildtype controls. Additionally, we investigated whether infection with Pseudomonas aeruginosa, a common pathogen in the CF lung, affected this important host defence mechanism.Ciliary beat frequency (fcb) and particle transport (PT) were recorded using an in vitro lung explant preparation. Measurements were made from uninfected cystic fibrosis transmembrane conductance regulator (CFTR) knockout (-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…This finding was not surprising, since we have been unable to detect an altered bioelectric phenotype in the trachea of the cftr tm1UNC CF mouse (14). However, in an in vitro study in which the University of North Carolina CF mouse was bred on a C57BL/6 background, the investigators reported a significant decrease in the rate of MCT (particle transport) in CF mice (5). In another study of CF mice (cftr m1HGU ), the investigators reported a significant decrease in the rate of MCT (39), although the rates of MCT in both normal and CF preparations were very low (see Table 1).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This finding was not surprising, since we have been unable to detect an altered bioelectric phenotype in the trachea of the cftr tm1UNC CF mouse (14). However, in an in vitro study in which the University of North Carolina CF mouse was bred on a C57BL/6 background, the investigators reported a significant decrease in the rate of MCT (particle transport) in CF mice (5). In another study of CF mice (cftr m1HGU ), the investigators reported a significant decrease in the rate of MCT (39), although the rates of MCT in both normal and CF preparations were very low (see Table 1).…”
Section: Discussionmentioning
confidence: 55%
“…There are published studies on measurement of lower airway MCT in the mouse by particle transport (3,5,19,39) and isotopic clearance (8). Values from these studies vary widely, and there is no method available for in vivo measurement of MCT in the nasal cavity of the mouse.…”
mentioning
confidence: 99%
“…Although this may be largely true, a variety of interesting observations have subsequently been made in the apparent absence of infection. These include excessive inflammation observed by histology in Cftr tm1Hgu mice [41], abnormal MCC in the Cftr tm1Hgu and Cftr tm1Unc mice [41,42], an increase in goblet cells, with decreased volume of airway surface liquid in the nasal epithelium of Cftr tm1Unc mice [43], a more distal extension of submucosal glands in Cftr tm1Hgu and Cftr tm1G551D mice [44], hypersensitivity of bone marrow-derived macrophages from Cftr tm1G551D mice to bacterial lipopolysaccharide (LPS) [45], and abnormalities in intracellular nitric oxide syntethase (iNOS) expression in Cftr tm1Unc and Cftr tm1Kth mice [46,47].…”
Section: Pathophysiological Changes In Murine Cf Airwaysmentioning
confidence: 98%
“…Furthermore, most of these CF mouse models retain defects in cAMP-inducible chloride permeability in the nasal epithelium as seen in humans. Though not extensively studied in each model, reports have suggested decreased mucociliary clearance (2224), reduced fertility (25, 26), mild pancreatic dysfunction (2729), and liver abnormalities (28). However, these models thus far lack the development of significant spontaneous lung disease as observed in humans with CF.…”
Section: Introductionmentioning
confidence: 99%